PENGARUH LAMA MARINASI KOMBINASI SARI PATI BUAH NANAS DAN PEPAYA TERHADAP PH DAN TEKSTUR DAGING AYAM KUB - Sutarso; Adyatama, Aqil (Fakultas Pertanian Universitas Garut, 2025)
KUB chicken as a type of meat poultry has high potential as livestock that produces meat that is rich in nutritional content. The processing carried out to improve the quality of KUB chicken meat is by adding enzymes through the marinating process. This study aims to determine the physical quality and tenderness of KUB chicken meat marinated with a combination of pineapple and young papaya fruit extract at different marinating times. This study was conducted in May 2025 in Karangkobar District, Banjarnegara Regency, Central Java Province. This study was conducted experimentally which was arranged based on a completely randomized design (CRD) with 4 treatments (0 minutes, 30 minutes, 45 minutes, and 60 minutes) which were repeated 5 times. The results of the analysis gave a very significant effect on the pH of KUB chicken meat (P <0.05). from various treatments P0 to P4 showed a gradual decrease in pH and along with the treatment given. Furthermore, the results of the analysis on meat texture proved that each treatment showed a significant change (P <0.05) in the texture of KUB chicken meat, with an increase in the average value along with the treatment given. The results showed that the P4 treatment of a combination of pineapple and papaya starch with a soaking time of 60 minutes proved to have a significant effect on the pH and texture of KUB Chicken meat.